Short-Term Changes in Anemia Prevention Knowledge, Attitudes, and Practices After Community-Based Health Education Among Adolescent Girls: IN PRESS - Wahyu Ratri Sukmaningsih; Anggraini Luthfiyyah Syarry Handoko; Dyah Ayu Pitaloka (Jurnal Ilmu Kesehatan Masyarakat, 2026)
Anemia remains a major public health concern among adolescent girls despite ongoing iron supplementation and screening programs. Health education may improve knowledge, attitudes, and preventive practices related to anemia prevention. This study aimed to assess changes in knowledge, attitudes, and preventive practices among adolescent girls following a health education program supported by leaflets and posters. A pre-experimental one-group pretest-posttest study was conducted from May to June 2026 among 100 female participants aged 17-20 years who were active members of Karang Taruna “Tunas Mekar” in Gondangrejo District, Karanganyar Regency, Indonesia. All eligible members were included through total sampling. Participants completed a validated and reliable questionnaire immediately before the intervention and seven days afterward. Paired scores were analyzed using the Wilcoxon signed-rank test, and effect sizes were calculated as r = Z/√N. Following the intervention, median knowledge, attitude, and preventive-practice scores increased from 10 (IQR 8-12) to 13 (IQR 12-14), 28 (IQR 25-31) to 33 (IQR 31-36), and 6 (IQR 5-7) to 8 (IQR 7-9), respectively. Significant differences were observed between pre-test and post-test scores for knowledge, attitudes, and preventive practices (all p < 0.001), with moderate effect sizes (r = 0.394-0.411). Short-term improvements in knowledge, attitudes, and self-reported preventive practices were observed following the health education program. These findings suggest that leaflet- and poster-assisted health education may be a practical component of community-based anemia prevention programs; however, controlled studies with longer follow-up are needed to confirm long-term effectiveness.